2007
DOI: 10.1530/rep.1.01091
|View full text |Cite
|
Sign up to set email alerts
|

Participation of phosphatidyl inositol 3-kinase/protein kinase B and ERK1/2 pathways in interleukin-1β stimulation of lactate production in Sertoli cells

Abstract: Interleukin-1b (IL1b) belongs to a set of intratesticular regulators that provide the fine-tuning of cellular processes implicated in the maintenance of spermatogenesis. The aim of the present study was to analyze the signaling pathways that may participate in IL1b regulation of Sertoli cell function. Sertoli cell cultures from 20-day-old rat were used. Stimulation of the cultures with IL1b showed increments in phosphorylated protein kinase B (PKB), P70S6K, and ERK1/2 levels. A phosphatidyl inositol 3-kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This conclusion arose from the observations made on the lack of effect of wortmannin, an inhibitor of PI3K, on glucose uptake. The latter results are somehow surprising considering that the PI3K/PKB pathway is widely used to regulate glucose uptake in response to several hormonal stimuli in Sertoli cells (27,35,36). On the other hand, results presented herein are in agreement with the observations made in muscle cells under conditions of hypoxia, where stimulation of glucose uptake independent of PI3K and involving an AMPK-dependent pathway has been observed (12,21,29,38).…”
Section: Ajp-endocrinol Metabsupporting
confidence: 84%
See 1 more Smart Citation
“…This conclusion arose from the observations made on the lack of effect of wortmannin, an inhibitor of PI3K, on glucose uptake. The latter results are somehow surprising considering that the PI3K/PKB pathway is widely used to regulate glucose uptake in response to several hormonal stimuli in Sertoli cells (27,35,36). On the other hand, results presented herein are in agreement with the observations made in muscle cells under conditions of hypoxia, where stimulation of glucose uptake independent of PI3K and involving an AMPK-dependent pathway has been observed (12,21,29,38).…”
Section: Ajp-endocrinol Metabsupporting
confidence: 84%
“…In addition, we have previously demonstrated that in Sertoli cells the PI3K/PKB signaling pathway participates in several responses to hormones, particularly in the regulation of glucose uptake into the cell (27,35,36).…”
mentioning
confidence: 99%
“…423 Regulation of Sertoli cell function by exogenous IL1 has been found to involve multiple pathway intermediates, including MAPK14, MAPK8 and MAPK3/MAPK1, PIK3/AKT, PTGS2/PGE 2 and NOS2/NO, although the more predictable participation of MYD88 and NFκB still awaits investigation. 417,[424][425][426][427]…”
Section: Intratesticular Actions Of Interleukin-1mentioning
confidence: 99%
“…IL1a-induced 3b-HSD2 mRNA levels were also found to be a result of activation of the PI3K signalling pathway. Although the PI3K pathway is not the most common target of IL1R1 transactivation, recent studies in rat Sertoli cells suggest involvement of this pathway in IL1 signalling cascades (Riera et al 2007). In addition, the PI3K pathway appeared to be a component in the effects of IL4 on 3b-HSD1 and 3b-HSD2 mRNA.…”
Section: Discussionmentioning
confidence: 97%